(untitled) (Costos y Gestión, 2019)
This paper addresses the costs management in the telecommunications sector, in order to identify strategies for the rationalization of costs incurred in this type of industry. It begins with a brief description of the general characteristics of the telecommunications sector in Colombia (types of service, competitive issues and market statistics). Then, it describes and analyzes particular concepts of telecom costs, such as "marginal cost", "incremental cost" (and its various calculation approaches), "historical costs", "looking forward costs" and "Subscriber Acquisition Cost - SAC". Based on the above, and taking as a criterion for prioritizing the weight of each type of cost in the typical cost structure of the telecommunications companies, are proposed and discussed a set of strategies aimed at reducing costs, focused in the two principal costs (SAC and Network OPEX). While these strategies are discussed, they are contextualized in the current environment of telecommunications companies in Colombia and in the world.